Protocol for a parallel assignment prospective, randomised, double-blinded, placebo-controlled trial to evaluate the efficacy of 0.01% atropine for near work-induced transient myopia and myopic progression in China - Sile Yu; Wei He; Lan Hu; Ling Xu; Jiayan Chen; Guanghao Qin; Yifan Qi; Emmanuel Eric Pazo; Xingru He (BMJ Open)
Introduction Assessment of near work-induced transient myopia (NITM) is important for permanent myopia development and progression. Atropine eye drop has been reported to be beneficial in reducing initial NITM and slowing down myopic progression. This study aimed to investigate the efficacy of 0.01% atropine in treating NITM and its possible association with the progression of refractive change in Chinese myopic children.Methods and analysis The study is designed as a parallel assignment prospective, randomised, double-blinded, placebo-controlled trial conducted at He Eye Specialist Hospital in Shenyang, China. One hundred fifty participants will be randomly assigned in a 1:1 ratio to receive 0.01% atropine or placebo eye drop once nightly bilaterally for 1 year. Initial NITM, cycloplegic refraction, axial length, best-corrected visual acuity, intraocular pressure and pupil diameter will be measured at baseline, 4 weeks, 12 weeks, 24 weeks, 36 weeks and 48 weeks. Visual Function Questionnaire will be administered at baseline and each follow-up visit. Adverse events also will be monitored and documented at each subsequent follow-up visit.Ethics and dissemination A parallel assignment prospective, randomised, double-blinded, placebo-controlled trial to evaluate the efficacy of 0.01% atropine for near work-induced transient myopia and myopic progression registered on 10 September 2023. Ethics approval number: IRB (2023) K025.01. The study’s findings will be shared regardless of the effect’s direction.Trial registration number NCT06034366.